ÃƒËœÃ‚ÂªÃƒËœÃ‚Â¹Ãƒâ„¢Ã…Â Ãƒâ„¢Ã…Â Ãƒâ„¢Ã¢â‚¬Â ÃƒËœÃ‚Â¬Ãƒâ„¢Ã‹â€ ÃƒËœÃ‚Â¯ÃƒËœÃ‚Â© ÃƒËœÃ‚ÂªÃƒËœÃ‚Â¹Ãƒâ„¢Ã¢â‚¬Å¾Ãƒâ„¢Ã…Â Ãƒâ„¢Ã¢â‚¬Â¦ ÃƒËœÃ‚Â§Ãƒâ„¢Ã¢â‚¬Å¾Ãƒâ„¢Ã¢â‚¬Å¾ÃƒËœÃ‚ÂºÃƒËœÃ‚Â© ÃƒËœÃ‚Â§Ãƒâ„¢Ã¢â‚¬Å¾ÃƒËœÃ‚Â¹ÃƒËœÃ‚Â±ÃƒËœÃ‚Â¨Ãƒâ„¢Ã…Â ÃƒËœÃ‚Â© Ãƒâ„¢Ã‚ÂÃƒâ„¢Ã…Â ÃƒËœÃ‚Â§Ãƒâ„¢Ã¢â‚¬Å¾Ãƒâ„¢Ã¢â‚¬Â¦ÃƒËœÃ‚Â¯ÃƒËœÃ‚Â±ÃƒËœÃ‚Â³ÃƒËœÃ‚Â© ÃƒËœÃ‚Â§Ãƒâ„¢Ã¢â‚¬Å¾ÃƒËœÃ‚Â«ÃƒËœÃ‚Â§Ãƒâ„¢Ã¢â‚¬Â Ãƒâ„¢Ã‹â€ Ãƒâ„¢Ã…Â ÃƒËœÃ‚Â© Ãƒâ„¢Ã‚ÂÃƒâ„¢Ã…Â ÃƒËœÃ‚Â£Ãƒâ„¢Ã¢â‚¬Â ÃƒËœÃ‚Â¯Ãƒâ„¢Ã‹â€ Ãƒâ„¢Ã¢â‚¬Â Ãƒâ„¢Ã…Â ÃƒËœÃ‚Â³Ãƒâ„¢Ã…Â Ãƒ - Fathi Hidayah; Mamluatu Solihah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
This research aims to reveal the steps of defining quality in the teaching of Arabic language. This research used qualitative approach by case study design to analyze the steps of defining quality in the teaching of Arabic language. To collect the data used observation, interview and documents. And to analyze the data used Milles and Hubberman analysis. The results of this research mean: (1) the steps of defining quality in the teaching of Arabic language in Madrasa Tsanawiya are: Planning step: setting goals, the rule for the teacher and supervisor, the process of teaching Arabic in the classroom, evaluation, language activities and language environment . Implementation step: The teaching process took place in the Arabic language by accomplishing the educational goals and teaching materials by teaching methods and media, and doing the evaluatio.. Evaluation step: doing the internal evaluation is the daily, weekly, monthly, and annual evaluation. Improvement step: by increase language activities.